Scaling oxygen consumption to body mass in real elite-cross country skiing performances - Carlsson, T.; Carlsson, M.; Hammarström, D.; Tonkonogi, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Maximal oxygen consumption (VO2max) is a frequently evaluated test parameter in cross-country skiing. Most often the units L min(-1) and mL min(-1) kg(-1) are used as performance ability markers, but earlier research have suggested that VO2max divided by body mass raised to 2/3 power would theoretically better reflect the physiological demands in cross-country skiing (Bergh and Forsberg, 1992). Changes in cross-country skiing in the last decades might place different physiological demands regarding VO2max. The purpose was therefore to find the optimal body mass exponent for test parameter VO2max for real elite cross-country skiing performances and ranking points. Methods: Four to seven days prior to the first ski race twelve highly motivated male Swedish national elite cross-country skiers (age 23.9+/-4.2 years; weight 76.2+/-5.8 kg; VO2max 5.34+/-0.34 L min(-1)) completed an incremental treadmill roller skiing test in diagonal technique determining VO2max. Performance data were collected from the Swedish National Championship (SNC) in cross-country skiing (13-17 March 2008): 15-km with individual start in classical technique (SNC15); 30-km double pursuit with mass-start (SNC30) also divided in the two halves in classical technique (SNC30:15c) and free-style technique (SNC30:15f); sprint prolog in free-style technique (SNCsprint). In addition to ski races, overall seasonal ski ranking points were collected from International Ski Federation`s (FIS) 3rd Cross-Country Points List 2007/2008 published before SNC for distance (FISdist) and sprint (FISsprint) races. Body mass scaling of VO2max for each of the skiing performances was determined using Pearson´s correlation analysis. Optimal mass exponent was set to the scaling value between zero (L min(-1)) and one (mL min(-1) kg(-1)) where Pearson`s product-moment correlation coefficient showed highest correlation for the relationship between VO2max and the ski performance parameter. Results: Optimal body mass exponents for VO2max regarding ski performances SNC15, SNC30, SNC30:15c SNC30:15f and SNCsprint were 0.49, 0.57, 0.55, 0.58 and 0.31, respectively. Optimal scaling factor for FISdist was 0.63 and corresponding value for FISsprint was 0.25. Discussion: This study indicates that optimal body mass exponents for maximal aerobic power depends mainly on work intensity of the actual skiing performance. Sprint skiing performance places higher metabolic demands than distance races which are reflected by a lower scaling factor. The fact that SNC15 had a lower optimal body mass exponent than SNC30:15c despite both were performed in the same course and technique supports the work intensity theory because in double pursuit the physiological resources should be sufficient to go 15-km more resulting in lower work intensity. Summarizing the reasoning above heavier skiers are favored in shorter race distances with higher metabolic demands.